Genetic variants and cell-free hemoglobin processing in sickle cell nephropathy - Saraf, S. L.; Zhang, X.; Shah, B.; Kanias, T.; Gudehithlu, K. P.; Kittles, R.; Machado, R. F.; Arruda, J. A. L.; Gladwin, M. T.; Singh, A. K.; Gordeuk, V. R. (Haematologica (Roma), 2015)
Intravascular hemolysis and hemoglobinuria are associated with sickle cell nephropathy. ApoL1 is involved in cell-free hemoglobin scavenging through association with haptoglobin-related protein. APOL1 G1/G2 variants are the strongest genetic predictors of kidney disease in the general African-American population. A single report associated APOL1 G1/G2 with sickle cell nephropathy. In 221 patients with sickle cell disease at the University of Illinois at Chicago, we replicated the finding of an association of APOL1 G1/G2 with proteinuria, specifically with urine albumin concentration (β=1.1, P=0.003), observed an even stronger association with hemoglobinuria (OR=2.5, P=4.3×10(-6)), and also replicated the finding of an association with hemoglobinuria in 487 patients from the Walk-Treatment of Pulmonary Hypertension and Sickle cell Disease with Sildenafil Therapy study (OR=2.6, P=0.003). In 25 University of Illinois sickle cell disease patients, concentrations of urine kidney injury molecule-1 correlated with urine cell-free hemoglobin concentrations (r=0.59, P=0.002). Exposing human proximal tubular cells to increasing cell-free hemoglobin led to increasing concentrations of supernatant kidney injury molecule-1 (P=0.01), reduced viability (P=0.01) and induction of HMOX1 and SOD2. HMOX1 rs743811 associated with chronic kidney disease stage (OR=3.0, P=0.0001) in the University of Illinois cohort and end-stage renal disease (OR=10.0, P=0.0003) in the Walk-Treatment of Pulmonary Hypertension and Sickle cell Disease with Sildenafil Therapy cohort. Longer HMOX1 GT-tandem repeats (>25) were associated with lower estimated glomerular filtration rate in the University of Illinois cohort (P=0.01). Our findings point to an association of APOL1 G1/G2 with kidney disease in sickle cell disease, possibly through increased risk of hemoglobinuria, and associations of HMOX1 variants with kidney disease, possibly through reduced protection of the kidney from hemoglobin-mediated toxicity.